α-Chaconine Affects the Apoptosis, Mechanical Barrier Function, and Antioxidant Ability of Mouse Small Intestinal Epithelial Cells - He, Yuhua; Chen, Jiaqi; Zhang, Qiyue; Zhang, Jialong; Wang, Lulai; Chen, Xiaoxia; Molenaar, Adrian J.; Sun, Xuezhao (Frontiers in Plant Science, 2021)
α-Chaconine is the most abundant glycoalkaloid in potato and toxic to the animal digestive system, but the mechanisms underlying the toxicity are unclear. In this study, mouse small intestinal epithelial cells were incubated with α-chaconine at 0, 0.4, and 0.8 μg/mL for 24, 48, and 72 h to examine apoptosis, mechanical barrier function, and antioxidant ability of the cells using a cell metabolic activity assay, flow cytometry, Western blot, immunofluorescence, and fluorescence quantitative PCR. The results showed that α-chaconine significantly decreased cell proliferation rate, increased apoptosis rate, decreased transepithelial electrical resistance (TEER) value, and increased alkaline phosphatase (AKP) and lactate dehydrogenase (LDH) activities, and there were interactions between α-chaconine concentration and incubation time. α-Chaconine significantly reduced the relative and mRNA expressions of genes coding tight junction proteins zonula occludens-1 (ZO-1) and occludin, increased malondialdehyde (MDA) content, decreased total glutathione (T-GSH) content, reduced the activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and γ-glutamylcysteine synthetase (γ-GCS) and the mRNA expressions of SOD, CAT, GSH-Px, and γ-GCS genes. In conclusion, α-chaconine disrupts the cell cycle, destroys the mechanical barrier and permeability of mucosal epithelium, inhibits cell proliferation, and accelerates cell apoptosis.